Magnifying endoscopy with narrow-band imaging for gastric heterotopic pancreas - Heetaek Oh; Gwang Ha Kim; Moon Won Lee; Hye Kyung Jeon; Dong Hoon Baek; Bong Eun Lee (Endoscopy International Open, 2018)
Background and study aims Heterotopic pancreas is a common subepithelial lesion in the stomach. However, its histological diagnosis is difficult when tissue samples are obtained with a conventional biopsy forceps. This study aimed to describe the magnifying endoscopy with narrow-band imaging (ME-NBI) features of gastric heterotopic pancreas. Patients and methods We retrospectively analyzed a database of all patients who underwent endoscopic ultrasonography (EUS) at Pusan National University Hospital from January 2010 to December 2010. Thirty-six patients with endosonographically diagnosed heterotopic pancreas who underwent ME-NBI and endoscopic ultrasonography (EUS) simultaneously were studied. The ME-NBI features of their lesions were analyzed. Results Thirty lesions were located in the antrum and six in the body. Six lesions (17 %) showed umbilication or central dimpling on the surface, and nine (25 %) had a macroscopic opening on the surface. On ME-NBI, a microscopic opening was identified in 22 (81 %) of 27 lesions wherein a macroscopic opening was not observed during conventional endoscopy. Macroscopic or microscopic opening was observed in 31 lesions (86 %). The frequency of macroscopic or microscopic opening was higher in lesions with anechoic duct-like structures than in lesions without such structures on EUS (91 % [29/32] vs 50 % [2/4], P = 0.027). Focal loss of microsurface structure and presence of a thickened submucosal vessel were observed in 6 (17 %) and 5 lesions (14 %), respectively. Conclusions The characteristic ME-NBI feature of heterotopic pancreas is presence of a microscopic opening on its surface. This ME-NBI feature is potentially useful for differentiating heterotopic pancreas from other gastric subepithelial tumors.